Carotid sinus hypersensitivity: block of the sternocleidomastoid muscle does not affect responses to carotid sinus massage in healthy young adults. Issue 19 (16th October 2017) - Lloyd, Matthew G.; Wakeling, James M.; Koehle, Michael S.; Drapala, Robert J.; Claydon, Victoria E.
Abstract: The arterial baroreflex is crucial for short‐term blood pressure control – abnormal baroreflex function predisposes to syncope and falling. Hypersensitive responses to carotid baroreflex stimulation using carotid sinus massage (CSM) are common in older adults and may be associated with syncope. The pathophysiology of this hypersensitivity is unknown, but chronic denervation of the sternocleidomastoid muscles is common in elderly patients with carotid sinus hypersensitivity (CSH), and is proposed to interfere with normal integration of afferent firing from the carotid baroreceptors with proprioceptive feedback from the sternocleidomastoids, producing large responses to CSM. We hypothesized that simulation of sternocleidomastoid "denervation" using pharmacological blockade would increase cardiovascular responses to CSM. Thirteen participants received supine and tilted CSM prior to intramuscular injections (6–8 mL distributed over four sites) of 2% lidocaine hydrochloride, and 0.9% saline (placebo) in contralateral sternocleidomastoid muscles. Muscle activation was recorded with electromyography (EMG) during maximal unilateral sternocleidomastoid contraction both pre‐ and postinjection. Supine and tilted CSM were repeated following injections and responses compared to preinjection. Following lidocaine injection, the muscle activation fell to 23 ± 0.04% of the preinjection value ( P  < 0.001), confirming neural block of the sternocleidomastoid muscles. Cardiac (RRI, RR interval), forearm vascular resistance (FVR), and systolic arterial pressure (SAP) responses to CSM did not increase after lidocaine injection in either supine or tilted positions (supine: ΔRRI −72 ± 31 ms, ΔSAP +2 ± 1 mmHg, ΔFVR +4 ± 4%; tilted: ΔRRI −20 ± 13 ms, ΔSAP +2 ± 2 mmHg, ΔFVR +2 ± 4%; all P  > 0.05). Neural block of the sternocleidomastoid muscles does not increase cardiovascular responses to CSM. The pathophysiology of CSH remains unknown. Abstract : Despite its high prevalence in the elderly, and reported association with devastating episodes of syncope and falls, the pathophysiology of carotid sinus hypersensitivity (CSH) remains unknown. Chronic denervation of the sternocleidomastoid muscles is common in elderly patients with (CSH), and is proposed to interfere with normal integration of afferent firing from the carotid baroreceptors with proprioceptive feedback from the sternocleidomastoids, producing large responses to carotid sinus massage. We showed that neural block of the sternocleidomastoid muscles with lidocaine does not increase cardiovascular responses to carotid sinus massage. These results suggest that the previously reported association between sternocleidomastoid denervation and CSH in older adults may be coincidental, rather than causal, and highlight the need for further research to identify the pathophysiological mechanisms underlying CSH.